Complex conductance of ultrathin La₂₋xSrxCuO₄ films and heterostructures - Gasparov, V.A.; Božović, I. (Физика низких температур, 2015)
We used atomic-layer molecular beam epitaxy to synthesize bilayers of a cuprate metal (La₁.₅₅Sr₀.₄₅CuO₄) and a cuprate insulator (La₂CuO₄), in which each layer is just one unit cells thick. We have studied the magnetic field and temperature dependence of the complex sheet conductance, σ(ω), of these films. Experiments have been carried out at frequencies between 2–50 MHz using the single-spiral coil technique. We found that: (i) the inductive response starts at ∆T = 3 K lower temperatures than Re σ(T), which in turn is characterized by a peak close to the transition, (ii) this shift is almost constant with magnetic field up to 14 mT; (iii) ∆T increases sharply up to 4 K at larger fields and becomes constant up to 8 T; (iv) the vortex diffusion constant D(T) is not linear with T at low temperatures as in the case of free vortices, but is rather exponential due to pinning of vortex cores, and (v) the dynamic Berezinski–Kosterlitz–Thouless (BKT) transition temperature occurs at the point where Y = (lω/ξ₊)² = 1. Our experimental results can be described well by the extended dynamic theory of the BKT transition and dynamics of bound vortex–antivortex pairs with short separation lengths.